Cerebral perfusion mediated by thalamo‐cortical functional connectivity in non‐dominant thalamus affects naming ability in aphasia. Issue 3 (26th October 2021) - Zhang, Jie; Zhou, Zhen; Li, Lingling; Ye, Jing; Shang, Desheng; Zhong, Shuchang; Yao, Bo; Xu, Cong; Yu, Yamei; He, Fangping; Ye, Xiangming; Luo, Benyan
Abstract: Naming is a commonly impaired language domain in various types of aphasia. Emerging evidence supports the cortico‐subcortical circuitry subserving naming processing, although neurovascular regulation of the non‐dominant thalamic and basal ganglia subregions underlying post‐stroke naming difficulty remains unclear. Data from 25 subacute stroke patients and 26 age‐, sex‐, and education‐matched healthy volunteers were analyzed. Region‐of‐interest‐wise functional connectivity (FC) was calculated to measure the strength of cortico‐subcortical connections. Cerebral blood flow (CBF) was determined to reflect perfusion levels. Correlation and mediation analyses were performed to identify the relationship between cortico‐subcortical connectivity, regional cerebral perfusion, and naming performance. We observed increased right‐hemispheric subcortical connectivity in patients. FC between the right posterior superior temporal sulcus (pSTS) and lateral/medial prefrontal thalamus (lPFtha/mPFtha) exhibited significantly negative correlations with total naming score. Trend‐level increased CBF in subcortical nuclei, including that in the right lPFtha, and significant negative correlations between naming and regional perfusion of the right lPFtha were observed. The relationship between CBF in the right lPFtha and naming was fully mediated by the lPFtha‐pSTS connectivity in the non‐dominant hemisphere. Our findings suggest that perfusion changes in the right thalamic subregions affect naming performance through thalamo‐cortical circuits in post‐stroke aphasia. This study highlights the neurovascular pathophysiology of the non‐dominant hemisphere and demonstrates thalamic involvement in naming after stroke. Abstract : We demonstrated that cerebral perfusion changes in the non‐dominant thalamic subregions affect naming performance through the thalamo‐cortical connectivity between the right lPFtha/mPFtha and pSTS in post‐stroke aphasia. Our findings highlight the pathophysiology of non‐dominant hemisphere recruitment, and that the right thalamic involvement of the lPFtha, from functional and vascular aspects, may underlie network reorganization for naming processing after stroke.